Marketing Strategy and Housing Purchase Decisions in Banjar: Purchasing Power and Purchase Intention - Maulida Jofadini; Eddy Yunus; Sri Utami Ady (Penerbit Goodwood, 2026)
Purpose: This study examines how four marketing mix strategies product, price, place, and promotion influence housing purchase decisions in Banjar Regency, with purchase intention as an intervening variable and purchasing power as a moderating variable.Methodology: This study employed a quantitative explanatory survey involving 300 housing buyers selected proportionally from active housing developers in Banjar Regency. Data were collected through a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine direct, mediation, and moderation relationships.Results: The findings indicate that price and promotion significantly enhance purchase intention, while product and place do not show significant effects. Price positively influences purchase decisions, whereas product has a significant negative direct effect. Purchase intention strongly determines purchase decisions and mediates the effects of price and promotion. Purchasing power significantly moderates the intention decision relationship, although the interaction effect is negative and weak.Conclusions: Housing purchase decisions are driven primarily by affordable pricing and intention formation rather than by product or location attributes alone.Limitations: The cross-sectional design and single-regency setting limit causal and geographic generalization.Contributions: This study contributes to property marketing research by demonstrating how marketing strategies operate through psychological intention under varying economic capabilities, providing a contextual extension of the marketing mix model in regional housing markets.